Using Blueprints to promote interorganizational knowledge transfer in digital health initiatives—a qualitative exploration of a national change program in English hospitals. (11th March 2021) - Williams, Robin; Sheikh, Aziz; Franklin, Bryony Dean; Krasuska, Marta; Nguyen, Hung The; Hinder, Susan; Lane, Wendy; Mozaffar, Hajar; Mason, Kathy; Eason, Sally; Potts, Henry W W; Cresswell, Kathrin
Abstract: Objective: The Global Digital Exemplar (GDE) Program is a national attempt to accelerate digital maturity in healthcare providers through promoting knowledge transfer across the English National Health Service (NHS). "Blueprints"—documents capturing implementation experience—were intended to facilitate this knowledge transfer. Here we explore how Blueprints have been conceptualized, produced, and used to promote interorganizational knowledge transfer across the NHS. Materials and Methods: We undertook an independent national qualitative evaluation of the GDE Program. This involved collecting data using semistructured interviews with implementation staff and clinical leaders in provider organizations, nonparticipant observation of meetings, and key documents. We also attended a range of national meetings and conferences, interviewed national program managers, and analyzed a range of policy documents. Our analysis drew on sociotechnical principles, combining deductive and inductive methods. Results: Data comprised 508 interviews, 163 observed meetings, and analysis of 325 documents. We found little evidence of Blueprints being adopted in the manner originally conceived by national program managers. However, they proved effective in different ways to those planned. As well as providing a helpful initial guide to a topic, we found that Blueprints served as a method of identifying relevant expertise that paved the way for subsequent discussions and richer knowledge transfers amongst provider organizations. The primary value of Blueprinting, therefore, seemed to be its role as a networking tool. Members of different organizations came together in developing, applying, and sustaining Blueprints through bilateral conversations—in some circumstances also fostering informal communities of practice. Conclusions: Blueprints may be effective in facilitating knowledge transfer among healthcare organizations, but need to be accompanied by other evolving methods, such as site visits and other networking activities, to iteratively transfer knowledge and experience.